Outer-shell photodetachment of the metastable Mg− [core]3s3p2 and Ca− [core]4s4p2 4Pe states (2008)
ABSTRACT: We report on calculated outer-shell photodetachment cross sections from the metastable (core)nsnp2 4Pe states in Mg− (n=3) and Ca− (n=4) negative ions in the photon energy range w=0–10 eV. Double-ionization thresholds for Mg II and Ca II as well as doubly excited thresholds of the residual atoms Mg I and Ca I are located within the photon energy range considered and thus doubly and triply excited states of both Mg− and Ca− are reached. We use a complex scaled configuration interaction (CSCI) method for the three active electrons supplemented with a sophisticated model potential as developed by Laughlin (Phys. Scr. 45, 238 (1992)) to account for core-valence interactions. The CI calculations are based on Mg+ and Ca+ one-electron orbitals expanded in terms of B-spline basis set. We compare our cross sections with the only calculation available up to a photon energy 0.25 Ry (w~3.4 eV) (Zeng et al., Phys. Rev. A 62, 022713(2000)) performed by using the R-matrix method, in which only one 4Po resonance for Mg− and two (4Po and 4Do) for Ca− were predicted. In this work, by analyzing both the cross sections and the locations of the S-matrix poles in the complex plane, we are able to predict six 4Po, four 4Do, and four 4So resonant states for Mg−, and three 4Po and two 4Do resonant states in Ca−.